The principles of the “smart city” concept as a determinant of urban policy - Stawasz, Danuta (Założenia koncepcji „smart city” wyznacznikiem dla polityki miejskiej, 2019)
The paper presents the principles of a "smart city" as an innovative approach aimed at managing public affairs in a city. First, selected definitions related to the concept of smart governance are presented, and then the thematic areas that are part of the principles of this concept are characterised. Further considerations focus on demonstrating that smart governance in the case of Polish cities requires redefining urban policy objectives, otherwise urban governance will be of a conservative nature, not responding to the needs of present and future generations of urban space users. The main directions of actions that should be reflected in the principles of urban policy so that Polish cities could make more dynamic their development processes, were also presented. One of them is the requirement of the continuous education of society towards the ability to use ICT techniques
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 101-107
Keywords: smart city concept; urban policy; urban development; koncepcja smart city; polityka miejska; rozwój miasta; smart city